Theory and Policy : A Commenton Dixit andon Current Tax Theory - Tanzi, Vito (IMF Working Papers; Working Paper ;, 1992)
In a recent paper Professor Dixit criticized the argument that when collection lags characterize tax systems, recourse to inflationary finance should be minimized. He argued that, in such case, rather than minimizing recourse to inflationary finance, the rates of the commodity taxes should be adjusted to maintain them at an optimal level and, thus, to minimize welfare costs. This paper shows that the requirements for following Dixit's policy prescription are almost impossible to meet. The paper argues that more attention should be paid by tax theorists to the constraints under which tax reforms are made.